A Strategy for Multivalent Presentation of Carba Analogues from N. meningitidis A Capsular Polysaccharide1. Issue 27 (20th August 2014) - Ramella, Daniela; Polito, Laura; Mazzini, Stefania; Ronchi, Silvia; Scaglioni, Leonardo; Marelli, Marcello; Lay, Luigi
Abstract: Neisseria meningitidis is a Gram‐negative encapsulated bacterium that is a major cause of meningitis and meningococcal septicemia. Serogroup A (MenA) is most often implicated in epidemic disease in the sub‐Saharan region of Africa. However, the development and manufacture of an efficient polysaccharide‐based vaccine against MenA is greatly hampered by the poor immunogenicity and instability of its capsular polisaccharide (CPS). We report the synthesis of stable MenA CPS carba analogues, and an easy strategy to access multivalent carbohydrate structures based on iron oxide nanoparticles (SPIONs). A 1‐ O ‐tetraethyleneglycol‐phosphate linker attached to the carba analogues was used to attach them to the metal surface. We evaluated the positive multivalent effect of the antigen presentation by MRI analysis, which showed that the conjugated monomer and dimer analogues could be recognised by the polyclonal anti‐MenA antibody. Abstract : Carba analogues of fragments of the N. meningitidis A polysaccharide have been proposed as hydrolytically stable analogues that have immunological activity in mice. Using the MRI technique, we found that when the carba analogues are loaded onto the surface of iron oxide nanoparticles, they show a multivalent effect that enhances their ability to be recognised by MenA antiserum.